Anti-androgenic and antifertility activity of Azadirachta indica seed oil in male albino rats - Ositadinma Sunday Onwuka; Chike Fidelis Oguejiofor; Ugochinyere Juliet Njoga; Izuchukwu Shedrack Ochiogu; Ifeanyi Gabriel Eke (Universitas Airlangga, 2026)
Two experimental phases (I and II) were conducted to investigate the reproductive effects of Azadirachta indica methanol seed extract (AIMSE) in adult male albino rats. In Phase I, male rats were randomly assigned (fourteen per group) to four groups: a control group (A) and three groups treated orally with graded doses of AIMSE at 50 mg/kg (B), 100 mg/kg (C) and 200 mg/kg (D) for 28 days. Animals were evaluated on day 0 (pre-treatment baseline), day 14 and day 28 for haematology, serum biochemistry and hormone concentrations, relative organ weights, sperm analysis and histopathology of the testis and epididymis. In Phase II, untreated fertile female rats were bred (four per group) with four male rats from each group (A-D) to assess post-treatment male fertility. Mated females were evaluated for several reproductive indices. In Phase I, AIMSE-treated males showed reduced serum testosterone concentrations, decreased vitality and motility of epididymal spermatozoa, and histopathological evidence of degeneration in the testis and epididymis. In Phase II, treatment with AIMSE for 28 days did not prevent mating by males and pregnancy in bred females; however, it induced significant antifertility effects, including decreased gestation index, reduced litter size and litter weight, increased pre-implantation loss, and decreased post-implantation embryo survival. These findings provide evidence of a dose-dependent in vivo anti-reproductive effects of AIMSE in male rats and, more importantly, a lowered fertility in females mated with treated males.